All Days 2008
DOI: 10.2118/118380-ms
|View full text |Cite
|
Sign up to set email alerts
|

A New Workflow for Comprehensive Petrophysical Characterization of Carbonate Reservoirs Drilled with Water-Base Muds

Abstract: One of the top concerns for carbonate reservoir evaluation is the effect of rock texture on permeability, capillary pressure and relative permeability. Recent advances in log analysis combined with new logging sensors that are sensitive to carbonate rock texture have led to an improved workflow for petrophysical analysis of carbonates. The authors have earlier described an approach to estimating permeability in carbonates from borehole NMR logs and electrical images, and have earlier studied the relationship b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…8 (Lima, et al, 2020). This correlation of the results makes it possible to partition the pores (e.g., Gyllensten et al, 2008).…”
Section: Pore Size Distribution Analysis Using T2 Distribution Graphsmentioning
confidence: 81%
See 1 more Smart Citation
“…8 (Lima, et al, 2020). This correlation of the results makes it possible to partition the pores (e.g., Gyllensten et al, 2008).…”
Section: Pore Size Distribution Analysis Using T2 Distribution Graphsmentioning
confidence: 81%
“…As noted earlier reported, only three samples were submitted to MICP tests based on the choice of Sgt values (high, medium, and low value), i.e., samples SD_35_03 (silurian dolomite), MC20P2 (coquina), and IL_09_05 (Indiana limestone). The throat size partitioning scheme described by Gyllensten et al (2008) was used to differentiate between different regions of the pore system: micropores from 0 to 0.5 µm, mesopores from 0.5 to 5 µm, and macropores above 5 µm.…”
Section: Pore Size Distribution Analysis Using T2 Distribution Graphsmentioning
confidence: 99%
“…It is also possible to have indications of an initial PC curve from the T2 distribution of Nuclear Magnetic Resonance (NMR) logs. The PC curve derived from NMR logs is equivalent of a drainage PC curve as described by Gyllensten et al (2008).…”
Section: Dynamics Of Invasionmentioning
confidence: 99%
“…Ramamoorthy et al (2008) and Gyllensten et al (2008) have demonstrated a workflow applicable to the Cretaceous carbonate reservoirs in the Middle East which exploits the information on rock texture available in borehole NMR and image logs along with conventional triple combo data and array resistivity data.…”
Section: Evaluation Workflow In Carbonatesmentioning
confidence: 99%
“…Recent field trials of an advanced dielectric logging tool and of a multi-dimensional NMR tool have shown that they provide very accurate saturations in the zone around the well-bore invaded by the mud filtrate Zielinski et al 2010). These tools have also been shown to provide textural information describing pore geometry (Gyllensten et al 2008).…”
Section: Introductionmentioning
confidence: 99%